Potentially Inappropriate Prescriptions to Older Patients in Emergency Departments in South Korea: A Retrospective Study - Kim K; Jung J; Kim H; Kim JT; Oh JM; Kim H (Dove Medical Press, 2021)
Kyungim Kim,1,2,* Jinyoung Jung,2,* Haesook Kim,3 Jung Tae Kim,4 Jung Mi Oh,5 Hyunah Kim6,7 1College of Pharmacy, Korea University, Sejong, Republic of Korea; 2Institute of Pharmaceutical Science, Korea University, Sejong, Republic of Korea; 3Department of Pharmacy, Gang Neung Asan Hospital, Gangneung, Republic of Korea; 4Department of Pharmacy, Kyung Hee University Hospital at Gangdong, Seoul, Republic of Korea; 5College of Pharmacy and Research Institute of Pharmaceutical Sciences, Seoul National University, Seoul, Republic of Korea; 6College of Pharmacy, Sookmyung Women’s University, Seoul, Republic of Korea; 7Drug Information Research Institute, College of Pharmacy, Sookmyung Women’s University, Seoul, Republic of Korea*These authors contributed equally to this workCorrespondence: Hyunah KimCollege of Pharmacy, Sookmyung Women’s University, Cheongpa-ro 47-gil 100, Yongsan-gu, Seoul, 04310, Republic of KoreaTel +82-2-2077-7961Email hyunah@sookmyung.ac.krPurpose: The purpose of this study was to evaluate the incidence of the administration of potentially inappropriate medications (PIMs) and the potential drug–drug interactions (pDDIs) in older patients in emergency departments (EDs) over a 12-month period and to identify the factors associated with the administration of PIMs.Patients and Methods: This retrospective study was conducted using the electronic medical records from two university-affiliated teaching hospitals in South Korea. ED visit cases of patients aged 65 and older from January 1, 2013, to December 31, 2013, were included in the analysis. Among the medications administered in ED, PIMs or pDDIs were identiﬁed using a drug utilization review program available in Korea.Results: During the study period, a total of 13,002 ED visit cases were reported from 10,686 patients. The proportion of ED visit cases with any PIM was 79.2% and the average number of PIMs was 2.7 (range, 1– 17). The most commonly administered PIMs that were contraindicated or should have been used with caution were ketorolac (41.3%) and metoclopramide (10.3%), respectively. Multivariate regression analysis indicated that female patients (p = 0.012), patients with more than six drugs in the ED (p < 0.001), and visits longer than 300 minutes (p = 0.026) were significantly associated with PIM administration in the ED. Potential DDIs between the medications administered in EDs were observed in 20.5% of total visit cases, with ketorolac being the most frequently reported drug in contraindicated drug combinations.Conclusion: This study demonstrated a high incidence of the administration of PIMs and medications with pDDIs in older patients in EDs and revealed the characteristics that are significantly associated with an increased risk of PIM administration. Healthcare providers in EDs should consider the risk of administering PIMs or medications with pDDIs, especially when treating older patients.Keywords: emergency department, older adults, potentially inappropriate medications, drug–drug interactions, drug utilization review